ANALISIS PENGARUH BETA SAHAM PERBANKANTERHADAP HARGA SAHAM PERBANKAN (Studi Pada Perusahaan Sektor Perbankan di Bursa Efek Indonesia periode 2010-2013) - Yuni Ekawarti (Universitas Indo Global Mandiri)
This research try to see the relationship between beta of the banking sector with stock prices of the banking sector. The goal of this research was to know the effect of beta formulation can uses by the investors to buy the stock of the banking sector at Indonesian Stock Exchange. This research uses the sample by taking the stock price banking period 2010-2013. Beta (β)is a systematic measure of risk of stock relative to market risk, knowing the beta of the security is important to analyse the securities. Knowing of beta is also useful for the consideration of incorporating such stocks into to the portofolio to be established. From this research indicate that there is significant influence between Beta and Banking stock price.Keyword:Beta, Investor, Banking stock price